Establishment of hydroponic root culture systems of Rhinacanthus nasutus and increased rhinacanthin production using elicitation technique - Thongtham Suksawat (Prince of Songkla University, 2024)
Doctor of Philosophy(Pharmaceutical Sciences), 2023